Reciprocal Filial Piety Facilitates Academic Success via Autonomy: Generalizing Findings in Chinese Society to a Global Context - Zhou, Jing; Guo, Qingke; Xu, Ruru (Frontiers in Psychology, 2020)
In cross-cultural psychology it is important to examine the universal (etic) and specific (emic) aspects of culture constructs. Filial piety is a core value of Chinese society that has shown related to psycho-social and academic development. This study was designed to investigate whether these relations revealed in specific cultural settings can be generalized to a global context. Using Chinese junior high school students as participants, Study 1 was intended to analyze the relations between filial piety and academic achievement, and whether autonomy need satisfaction serves as a bridge between them. Study 2 was designed to examine whether these psycho-social and academic benefits of filial piety can be applicable to a global context via analyzing two country-level databases (i.e. WVS and PISA). The results of Study 1 showed that reciprocal filial piety was positively associated with academic achievement via the satisfaction of the need for autonomy, while authoritarian filial belief did not have such effects. The results of Study 2 showed that, in a global context reciprocal filial belief in a society was related to the endorsement of autonomy, which in turn positively related to students’ academic achievement in that society, while authoritarian filial belief also did not show such effects. These findings suggest that some psychological constructs established in non-Western settings can also be applied to a global context.